Physical Condition Comparison between Female Athlete Indoor Hockey of East Java Team and National Team - Oemar, Fitry Nachamory; Subagio, Irmantara; Setiawan, Hayuris Kinandita; Rejeki, Purwo Sri (Folia Medica Indonesiana, 2021)
ABSTRACT The purpose of this research is to describe the physical condition differences between female athletes indoor hockey of East Java Team and National Team. Data sampling is taken from 12 female athletes indoor hockey of PON 2016 with age range 17-28 years old and 12 athletes of indoor hockey of Indonesia's National Team at SEA Games 2017 with age range 19-28 years old for comparison. Physical condition that measured is VO2max to represent endurance, abdominal muscle strength, speed and flexibility. Obtained data is then analyzed using SPSS. VO2max of East Java Team is (39.54±4.18) ml/kg/minute and for National Team is (43.43±7.59) ml/kg/minute (Ï=0.14). For abdominal muscle strength, East Java Team has (41.50±7.01) kg and National Team has (51.83±3.32) kg (Ï=0.00). For Speed, East Java Team has (3.59±0.30) second and National Team has (3.94±0.38) second (Ï=0.51). For Flexibility, East Java Team has (23.75±5.10) cm and National Team has (29.50±4.91) cm (Ï=0.01). From these data we can conclude that East Java Team physical condition is under National Team and it has significant differences at flexibility and abdominal muscle strength. Furthermore, optimal interventions are needed to improve both of those physical conditions. Keywords: hockey, endurance, flexibility, strength, speed